2017
DOI: 10.1021/jacs.7b09358
|View full text |Cite
|
Sign up to set email alerts
|

Total Syntheses of (+)- and (−)-Tetrapetalones A and C

Abstract: Described herein are syntheses of the naturally occurring polyketides (-)-tetrapetalones A and C and their respective enantiomers. The employed strategy involves initial assembly of a masked N-aryl tetramic acid which is advanced via a highly selective conjugate addition/intramolecular Friedel-Crafts acylation sequence to deliver a key azepine intermediate. Application of recently developed C-H activation chemistry and subsequent Heck cyclization delivers the aglycone framework in an overall 12 steps. Resoluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 33 publications
0
13
1
Order By: Relevance
“…(+)-Tetrapetalones A (193) and C (194) act as serine-βlactamase inhibitor as well as lipoxygenase inhibitor. In 2017 Wood et al [57] reported the total synthesis of (+)-tetrapetalones A (193) and C (194) where precursors 191 a/b were exposed to Heck reaction conditions under heating (24 h) or microwave (8 h) to furnish advance intermediates 192 a/b in good yield (Scheme 20). In 2016, Wong et al [58] also have adopted Pdcatalyzed intramolecular Heck reaction to prepare compound 196 from precursor 195 which was the essential intermediate to complete the total synthesis of bioactive plakortin polyketide (�)-gracilioether F (197) (Scheme 20).…”
Section: Polyketidesmentioning
confidence: 99%
See 1 more Smart Citation
“…(+)-Tetrapetalones A (193) and C (194) act as serine-βlactamase inhibitor as well as lipoxygenase inhibitor. In 2017 Wood et al [57] reported the total synthesis of (+)-tetrapetalones A (193) and C (194) where precursors 191 a/b were exposed to Heck reaction conditions under heating (24 h) or microwave (8 h) to furnish advance intermediates 192 a/b in good yield (Scheme 20). In 2016, Wong et al [58] also have adopted Pdcatalyzed intramolecular Heck reaction to prepare compound 196 from precursor 195 which was the essential intermediate to complete the total synthesis of bioactive plakortin polyketide (�)-gracilioether F (197) (Scheme 20).…”
Section: Polyketidesmentioning
confidence: 99%
“…(+)‐Tetrapetalones A ( 193 ) and C ( 194 ) act as serine‐β‐lactamase inhibitor as well as lipoxygenase inhibitor. In 2017 Wood et al [57] . reported the total synthesis of (+)‐tetrapetalones A ( 193 ) and C ( 194 ) where precursors 191 a/b were exposed to Heck reaction conditions under heating (24 h) or microwave (8 h) to furnish advance intermediates 192 a/b in good yield (Scheme 20).…”
Section: Polyketidesmentioning
confidence: 99%
“…Here, glycosylation also gave some amount of another diastereomer 416 , which was utilized for the synthesis of another isomer of the natural product (−)‐tetrapetalone A in a few steps (Scheme 48). [112] …”
Section: Application In Natural Product Synthesismentioning
confidence: 99%
“…Here, glycosylation also gave some amount of another diastereomer 416, which was utilized for the synthesis of another isomer of the natural product (À )-tetrapetalone A in a few steps (Scheme 48). [112] Zheng et al reported the total synthesis of caesalpinnone A, starting from resorcinol. Key features of the strategy were organocatalyzed [4 + 2] cycloaddition, trans-selective nucleophilic substitution, oxa-Michael addition, and photo-Fries rearrangement reactions.…”
Section: Application In Natural Product Synthesismentioning
confidence: 99%
“…Tetramic acid (pyrrolidine-2,4-dione) units are common in the secondary metabolites of microorganisms and frequently have an acyl substituent at position 3 to afford 3-acyl tetramic acid. Natural products or bioactive molecules containing the 3-acyl tetramic acid motif exhibit a variety of biological activities, including antibacterial, antiviral, and anticancer activities. Among these activities, antibacterial activity is of particular interest because 3-acyl tetramic acid was recently reported to play a crucial role in the quorum sensing of Gram-negative bacteria. The isoprenyl group of griseofamine A is also an intriguing fragment, as this motif has been shown to improve the interactions between small molecules and proteins …”
mentioning
confidence: 99%